Molecular and serological characterization of Leptospira kirschneri serogroup Pomona isolated from a human case in a Brazilian rural area - Balassiano, Ilana Teruszkin (2017)
Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Laboratório de Zoonoses Bacterianas. Centro de Referência Nacional para Leptospirose. World Health Organization/Pan American Health Organization. Centro Colaborador para Leptospirose - Coleção de Leptospira. Rio de Janeiro, RJ. Brasil..